Mediation effect of debt behaviour on Malaysian employees' financial strain moderated by job satisfaction - A. R., Husniyah; Z., Nurul Fardini; M., Amirah Shazana; S, Mohd. Fazli; S., Zahariah; O., Mohd. Amim (Human Resource Management Academic Research Society, 2022)
Recession and currently the unfolding pandemic COVID-19 do greatly impact most households economically. Individuals faced uncertainty affecting them in various aspects of life leading to stressful situation. The Expected Utility Theory supported this study aiming to identify factors affecting financial strain and the mediating effect of debt behaviour including the moderating effect by job satisfaction. A multi-stage random sampling among Malaysian employees resulted in 322 usable forms. External locus of control and debt attitude were found to be significantly affecting financial strain of employees. Mediation effect of debt behaviour was confirmed in the influence by debt attitude. Job satisfaction was found to moderate the influence of debt behaviour on the financial strain. Thus, employees should be concerned with their debt management as it can reduce financial strain. Ensuring high job satisfaction should be the focus of employers to multiply the effect of positive debt behaviour in reducing the financial strain.